Dramatic Clinical Improvement With Biotin Mega‐Dose Therapy in a Neonate With Holocarboxylase Synthetase Deficiency - Seon Woo Kim; Hyeon Joo Lee; Naye Choi; Ee‐Kyung Kim; Jung Min Ko (Molecular Genetics & Genomic Medicine)
ABSTRACT Introduction Holocarboxylase synthetase deficiency (HLCS deficiency, OMIM #253270) is an exceedingly rare metabolic disorder resulting in multiple carboxylase deficiencies owing to impaired biotin cycle. Clinical manifestations include severe metabolic acidosis, hyperammonemia, tachypnea, skin rash, alopecia, feeding problems, hypotonia, developmental delay, seizures, and, in severe cases, death. Methods and Results An 8‐day‐old female neonate presented with severe lactic acidosis, necessitating sedation and mechanical ventilation. Despite receiving supportive care, no evident clinical improvement was observed, accompanied by the onset of generalized ichthyosis. Genetic analysis of actionable metabolic disorders revealed compound heterozygous variants of HLCS (NM_000411.8), specifically c.[710T>C (p.Leu237Pro)]; [1544G>A (p.Ser515Asn)], prompting the initiation of biotin mega‐dose therapy (10 mg/day). Remarkably, dramatic clinical improvement in lactic acidosis was observed the day after initiating biotin administration, leading to the discontinuation of mechanical ventilation within 6 days. The patient remained in stable condition during follow‐up, exhibiting normal growth and development along with consistently stable laboratory findings up to 18 months of age. Conclusion Our case highlights the significance of early genetic testing in neonates with unexplained metabolic disorders to enable timely diagnosis and therapy initiation. Biotin therapy has demonstrated remarkable efficacy in improving the clinical condition of patients with HLCS deficiency, leading to favorable outcomes.